Strengthening the Character of Students Through Internalization of Islamic Educational Values During the Khulafaur Rasyidin Era: Modern Education - Armedi, Rama; Hasanah, Muslimatul; Nabila, Ahsana (Mu'allim, 2025)
Character education in Indonesia faces serious challenges due to the negative behavior of students, such as bullying, fighting, and rule violations. This phenomenon shows moral degradation that requires appropriate educational solutions. This research aims to analyze the relevance of Islamic education values during the Khulafaur Rashidin period as a strengthening of students' character in the modern era. The method used is descriptive qualitative through a literature study approach, by analyzing literature related to Islamic education values and their application in the current educational context. The results showed that the values of morality, justice, care, and wisdom taught by the caliphs, such as Abu Bakar Ash Shiddiq, Umar bin Khattab, Uthman bin Affan, and Ali bin Talib, are still very relevant to be internalized in modern character education. Active learning methods, such as discussions and social activities, can be used to teach these values. This research is expected to provide guidance for educators in shaping the character of ethical and responsible learners, as well as creating a more effective and meaningful learning environment.